Presupposition and miscommunication in the movie While You Were Sleeping (1995) by Jon Turteltaub - Sekar Dwi Pratiwi; Sari Rejeki; Resty Widya Kurniasari (Universitas Pakuan, 2026)
The effectiveness of communication is influenced by the assumptions held by speakers, which called presuppositions. Presupposition contained in an utterance must be accompanied by common ground. Common ground is the similarity of assumptions had by the speakers. The use of presupposition is founded in characters utterances in the movie While You Were Sleeping. This research aims to identify and interpret presuppositions in the characters utterances in the movie While You Were Sleeping, and additionally to describe its contextual meanings. The data was analyzed using the referent and pragmatic method. George Yule’s theory was used to analyze the presuppositions found in this research. 36 data were found in this research. 30 data of presupposition utterances are not accompanied by common ground between the speakers. Misunderstandings often arise in the movie While You Were Sleeping due to the absence of shared knowledge among the characters. Misunderstandings cause ineffective communication.